Productividad y oxigenación en la cuenca de panamá, pacífico colombiano, durante el pleistoceno tardío-holoceno: el registro de los foraminíferos bentónicos (2001)
Benthonic Foraminifera in the and gt; 150 µm size-fraction were analysed from the uppermost 2 m of Cores ODP677B (1.202oN-83.737oW) and TR163-38 (1.337oS-81.583oW) from the Panamá Basin, Colombian Pacific. A large seasonality in the organic carbon flux to the seafloor is suggested for Core ODP677B, -located in the mesotrophic central Panamá Basin-, for the last 30ka. Maximum values are recorded at 10.5 y 21 ka y 25.5 Y 30.5ka. Seasonality in the organic carbon flux to the seafloor is low and homogeneous for Core TR 163-38, -located in the southern eutrophic region of the Panamá Basinexcept for dysoxic-anoxic conditions between 10.5 and 18ka (the deglaciation) when productivity was intensified. These cores do respond to a productivity latitudinal gradient with similar or lower values in the north (Core ODP677B) than today's for the last glacial. Past productivity was larger during deglaciation south of the equator (Core TR163-38). Possible mechanisms to explain these trends are: (1)intensification of the Equatorial Divergence and Peruvian upwelling systems, (2) a more efficient utilization of nutrients, (3) variations in the chemical composition of upwelling waters, and (4) migration of the Equatorial Divergence.